(untitled) (Journal of Environmental Science and Natural Resources, 2013)
Allamanda leaf extracts were made by three organic solvents hexane, methanol and ethyl acetate having different polarities. Thin layer chromatography (TLC) of the refluxing extracts showed each of them contained considerable number of different compounds. By observing Rf value of these extracts it was confirmed that the compounds present in different extracts are not same and two of them (methanol and ethyl acetate) extracts were distilled to remove solvent for bioactivity test. In growth inhibition test, methanol and ethyl acetate extracts of allamanda inhibited mycelial growth of Phomopsis vexans. Ethyl acetate extract at 0.2% and 0.3% concentration inhibited 100% mycelial growth of Phomopsis vexans while methanol extract was not effective in suppressing growth rather it arrested temporarily the growth of Phomopsis vexans. Eggplant seeds treated with ethyl acetate extract in blotter produced higher percentage of seed germination (85.00%) and healthy seedlings (88.36%) and lower percentage of dead seed (15.00%), and rotten seed (5.89%) than those treated with methanol extract. In most cases, seed quality was improved with the increasing of concentration of ethyl acetate extract. It may be summarized that higher amount of antifungal compounds were present in ethyl acetate extract in purified form where methanol also have some compounds that inhibited partially growth of Phomopsis vexans. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14814 J. Environ. Sci. & Natural Resources, 5(2): 199-203 2012